Comparison Between 5- and 1-Year Outcomes Using Cutoff Values of Pressure Drop Coefficient and Fractional Flow Reserve for Diagnosing Coronary Artery Diseases - Banerjee, Rupak K.; Ramadurai, Sruthi; Manegaonkar, Shreyash M.; Rao, Marepalli B.; Rakkimuthu, Sathyaprabha; Effat, Mohamed A. (Frontiers in Physiology, 2021)
Background: The current pressure-based coronary diagnostic index, fractional flow reserve (FFR), has limited efficacy in the presence of microvascular disease (MVD). To overcome the limitations of FFR, the objective is to assess the recently introduced pressure drop coefficient (CDP), a fundamental fluid dynamics-based combined pressure-flow index. Methods: We hypothesize that CDP will result in improved clinical outcomes in comparison to FFR. To test the hypothesis, a Chi-squared test was performed to compare percent major adverse cardiac events (%MACE) at 5-years between a) FFR<0.75 and CDP>27.9 and b) FFR<0.80 and CDP>25.4 groups, using a prospective cohort study. Further, Kaplan Meier survival curves were compared between the FFR and CDP groups. Results were considered statistically significant for p<0.05. Outcomes of CDP-arm were presumptive as the clinical decision was solely based on the FFR. Results: For the complete patient group, the %MACE in the CDP>27.9 group (10 out of 35, 29%) was lower in comparison to the FFR<0.75 group (11 out of 20, 55%), and the difference was near significant (p=0.05). Survival analysis showed a significantly higher survival rate (p=0.01) in the CDP>27.9 group (n=35) when compared to the FFR<0.75 group (n=20). Results remained similar for FFR = 0.80 cut-off. Comparison of the 5-year MACE outcomes with the 1-year outcomes for the complete patient group showed similar trends with a higher statistical significance for a longer follow-up period of 5-year. Conclusion: Based on the MACE and survival analysis outcomes, CDP could possibly be an alternate diagnostic index for decision-making in the cardiac catheterization laboratory.